ACTIVE SUSPENSION SYSTEM DESIGN OF RAILWAY VEHICLE WITH H2 CONTROL THEORY - SORNONG MAULANA (NIM : 10104047); Dosen Pembimbing : Prof. Dr. Roberd Saragih
In many countries, railway vehicle were an essential transportation, because it was more efficient, fast, and inexpensive. However, there is some point that must be fixed, such as there were still a lot of train accident because of a bad suspense system and complain about heavy vibration in the train, so it makes passengers feel uncomfortable. Hence, a control system design that can minimized external or internal disturbance for a train is needed. In control system design, robustness of the system against noise is an important factor that must be reckoned. One type of robust control against disturbance is control H2. This final task discussed about control H2 and its application on railway vehicle model, where the suspension on this issue is active suspension. The main objective to be achieved is designing control, so vibration or disturbance that occurred on the railway system is minimal. First, mathematical model from the railway system will be derived, and then state space will be derived. After that, combining plant with the weighting functions will get the generalized plant. Next, an optimal controller using H2 control theory will be designed. And from the simulation result obtained that the H2 control effective to reduce interference with the suspension system.